International trade and polarization in the labor market - Satya P. Das (Kiel Institute for the World Economy (IfW), 2011)
The paper builds an argument that international trade can be one explanation behind polarization of employment in the labor market observed in developed countries such as U.K. and U.S. It considers a small open economy, having production sectors which use three types of labor: high-skill, middle-skill and low-skill. The economy faces an increase in the relative price of the high-skill intensive sector. Using decision rules for choosing middle-skill and low-skill education, it is shown that such a terms of trade shock can lead to higher shares of high-skill as well as low-skill workers in the total workforce. The effects off-shoring on wages and job composition are also studied. That of low-skill and high-skill tasks, not middle-skill tasks, is shown to contribute towards polarization in job composition.
Keywords: F16; J21; 330; polarization in labor markets; hollowing out; skill biased technical change; terms of trade; off-shoring